2022
DOI: 10.31219/osf.io/k5dzr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overperception of moral outrage in online social networks inflates beliefs about intergroup hostility

Abstract: As individuals and political leaders increasingly interact in online social networks, it is important to understand how the affordances of social media shape social knowledge of morality and politics. Here, we propose that social media users overperceive levels of moral outrage felt by individuals and groups, inflating beliefs about intergroup hostility. Utilizing a Twitter field survey, we measured authors’ moral outrage in real time and compared authors’ reports to observers’ judgments of the authors’ moral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Amplification in the evaluation of collective emotion also leads to the formation of social ties that express stronger emotions. Research on the perception of average collective emotions suggest that people tend to overestimate the intensity of fellow group members' positive and negative emotions in response to political issues (Brady et al, 2022;Goldenberg, Abruzzo, et al, 2022;Lau et al, 2016). Furthermore, in a recent study we found that the tendency to overestimate the collective emotional response was associated with selecting tie who express more extreme emotions.…”
Section: Cognitionmentioning
confidence: 62%
“…Amplification in the evaluation of collective emotion also leads to the formation of social ties that express stronger emotions. Research on the perception of average collective emotions suggest that people tend to overestimate the intensity of fellow group members' positive and negative emotions in response to political issues (Brady et al, 2022;Goldenberg, Abruzzo, et al, 2022;Lau et al, 2016). Furthermore, in a recent study we found that the tendency to overestimate the collective emotional response was associated with selecting tie who express more extreme emotions.…”
Section: Cognitionmentioning
confidence: 62%
“…Thus, this disconnect reflects a form of pluralistic ignorance (Miller & McFarland, 1991), wherein individuals systematically misperceive public opinion by overestimating how much it differs from their own. Indeed, such misperceptions of public opinions have been shown in other domains such as climate change (Leviston et al, 2013; Sparkman et al, 2022), alcohol consumption (Prentice & Miller, 1993), and political hostility (Brady et al, 2023; Moore-Berg et al, 2020; Ruggeri et al, 2021). Collectively, these results demonstrate that endorsement of redistributive vaccine policies enhances public trust in leaders and suggest that an accurate understanding of public opinion by policymakers is crucial for the containment and prevention of current and future health crises and resource shortages.…”
Section: Discussionmentioning
confidence: 99%
“…Overrepresentation of negative information, such as negative news or online hate, cultivates a more negative or dangerous evaluation of the world (Gerbner, Gross, Morgan, Signorielli, & Shanahan, 2002), potentially leading to a decrease in social trust (Näsi et al, 2015), and reduction in subjective well-being (Feinberg, Ford, Thai, Gatchpazian, & Lassetter, 2020;Keipi, Räsänen, Oksanen, Hawdon, & Näsi, 2018). In addition, exposure to negative political content has negative collective consequences such as contributing to group polarization and intergroup conflicts (Brady et al, 2022;de Mello et al, 2022). Based on the findings of this study, the overrepresentation of negative content produced by public figures could worsen over time, because increased sharing of negative content incentivizes public figures to produce more of this negative content (Brady, McLoughlin, Doan, & Crockett, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Overexposure to negativity is known to have adverse consequences at the individual level, leading to reduction in well-being (Diener et al, 2010;Jose, Lim, & Bryant, 2012;Seidlitz & Diener, 1993). At the collective level too, exposure to negativity contributes to group polarization and intergroup conflicts (Brady et al, 2022;de Mello, Cheung, & Inzlicht, 2022). Therefore, it is crucial to understand the roots of negativity sharing online and its driving mechanisms.…”
Section: Negativity Increases Sharing More For Public Figures Than Fo...mentioning
confidence: 99%